Rôle joué par l’économie informelle dans l’appropriation des TIC en milieu urbain en Afrique de l’Ouest - Annie Cheneau-Loquay (Netcom)
The “informal” economy concerns activities directly bound to the most contemporary evolutions. Those related with the insertion of the ICTs in territories are demonstrations of a “paradoxical invention of the modernity” [JF Bayart 1994] with regard to the universalist classic model of the modernization spread by the West. Having explained briefly what we understand by “informal” according to various disciplinary approaches, we shall show how the insertion and the appropriation of the ICTs in the African cities gives place to a proliferation of new activities of service which are embedded in the urban fabric, adapt themselves to the low level of income of the populations and generate more or less qualified jobs which recover totally or partially from informal practices. We shall wonder finally about the proliferation of this “other economy” expression of the globalization.